Navigating autonomy, privacy, and ageism in robot home care with aged users: A preliminary analysis of ROB-IN - Liedo, Belen (Bioethics, 2025)
In this article, I propose an ethical analysis of assistive domestic robots for older users. In doing so, I illustrate my inquiry with the example of ROB-IN assistive robot. ROB-IN is a Spanish project which is devoted to developing a robot that will perform in the private home of nondependent, aged users. It is aimed to help people in their daily activities and contribute to appropriate health monitoring. One of their potentially most useful features is related to data gathering and sharing. For the inquiry on the ethical underpinnings of this case, I develop a framework for domestic assistive robots for competent older adults drawn on the ethics of care. I assess that this type of robots could be ethically appraised attending to their impact on the well-being and autonomy of users. I approach autonomy from a relational perspective, and I delve into the relationship between autonomy and well-being through the concept of paternalism. I argue that this type of assistive robots should never act paternalistically. Given ROB-IN great implications regarding privacy, I subsequently explore the ways in which the privacy of users should be respected in their interaction with assistive robots, focusing on the relation with autonomy and well-being. Lastly, I highlight the need for avoiding ageism. This investigation focuses on aged users, but it is suggested that the situation of caregivers should be also the object of further investigations.